2012
DOI: 10.1186/1756-3305-5-298
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Schistosoma haematobium egg output and associated infection parameters following treatment with praziquantel in school-aged children

Abstract: BackgroundPraziquantel is the drug of choice in preventive chemotherapy targeting schistosomiasis. Increasing large-scale administration of praziquantel requires monitoring of drug efficacy to detect early signs of development of resistance. Standard protocols for drug efficacy monitoring are necessary. Here, we determined the optimal time point for praziquantel efficacy assessment against Schistosoma haematobium and studied the dynamics of infection parameters following treatment.MethodsNinety school-aged chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 50 publications
(69 reference statements)
6
38
3
Order By: Relevance
“…In the current study, the morbidity parameters, such as haematuria, proteinuria and pyuria (leucocytes) were associated with S. haematobium infection, and this agrees with work done by Gryseels et al (2006) [1], Stete et al [39], Mekonnen et al [40] and Wami et al [41], who also reported the association between haematuria, proteinuria and pyuria with urogenital schistosomiasis. The percentage increase in proteinuria (from 19.19% to 71.4%) and the decrease in haematuria (from 76.2% to 57.1%) in follow-up samples could be attributed to the activity of praziquantel in the body.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, the morbidity parameters, such as haematuria, proteinuria and pyuria (leucocytes) were associated with S. haematobium infection, and this agrees with work done by Gryseels et al (2006) [1], Stete et al [39], Mekonnen et al [40] and Wami et al [41], who also reported the association between haematuria, proteinuria and pyuria with urogenital schistosomiasis. The percentage increase in proteinuria (from 19.19% to 71.4%) and the decrease in haematuria (from 76.2% to 57.1%) in follow-up samples could be attributed to the activity of praziquantel in the body.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the mean egg count at the baseline being higher than that of the subsequent follow-ups agrees with a study conducted in the Cote d'Ivoire, which reported a higher mean egg count of 84.8 eggs/10 mL at the baseline, relative to a range of 40.5 to 0.3 eggs/10mL in the post-treatment phase [39]. However, the observation of eggs shed even after weeks of treatment in this study does not imply that the praziquantel treatment was ineffective and, thus, clinicians should not be very worried if eggs are detected in the laboratory, even after they have treated the patients.…”
Section: Discussionsupporting
confidence: 92%
“…Limitations of the original studies related to the diagnosis of Plasmodium and Schistosoma infection could also affect the present results [44,45]. In addition, some studies which examined S .…”
Section: Discussionmentioning
confidence: 95%
“…Due to its simplicity, syringe filtration is preferred in community and school surveys and requires less equipment than urine concentration with centrifugation. Similar to stool smear testing for fecal eggs, these tests are also prone to low sensitivity (74), although the eggs can generally be identified readily, as a relatively large volume of urine is used and there is an absence of the disturbing solid materials found in stool (42). Indeed, KK and urine egg detection techniques are particularly compatible in environments with high schistosome transmission levels, in light of their simplicity and cost-effectiveness.…”
Section: Direct Parasitological Diagnosismentioning
confidence: 99%